(untitled) (Research, Society and Development, 2022)
This article seeks to work on concepts and practices of computational thinking for problem solving by students at a high school in the municipality of Panambi, Rio Grande do Sul. They aim to operate the four pillars of computational thinking, which are abstraction, by encouraging students to read problems and identify what is important; decomposition, which allows students to divide the problem into smaller parts; pattern recognition, encouraging students to recognize patterns they have already used in similar problems, and algorithms, which seek to establish a set of steps to solve the problem. To complement the methodological path, the study relies on applied research, with a qualitative approach, which includes a complex network of terms, concepts and assumptions, related to cultural and interpretive studies, with a view to learning computational thinking. The research findings point to a qualified teaching and learning process, by presenting more than 50% of the activities carried out efficiently, contemplating the concepts presented, even if the students live with traditional methodologies, which glimpses the potential of thinking computational, in pedagogical practices, identifying the protagonism of the students.